Javascript novice to ninja - Jones, Darren (SitePoint, 2014)
Learn JavaScript from scratch! Packed with numerous examples, JavaScript: Novice to Ninja is a fun, step-by-step and comprehensive introduction to development in JavaScript. Discover how to use JavaScript to solve real-world problems, build smarter forms, track user events, and design eye-catching animations. Learn JavaScript's built-in functions, methods, and properties.Use JavaScript to validate form entries and interact with your users.Understand how to respond to user events and add interactivity to your applications.Create animations that bring your web site to life. Start programmi.
Includes bibliographical references. - Print version record
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)